Giving in dictator games: Experimenter demand effect or preference over the rules of the game? - Nadine Chlaß; Peter G. Moffatt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2012)
Traditionally, giving in dictator games was assumed to signal preferences over others' payoffs. To date, several studies find that dictator game giving breaks down under conditions designed to increase dictators' anonymity or if an option to take money obscures the purpose of the task. Giving is therefore argued to result from an experimenter demand effect. Here, we put this new interpretation to a stress test and find evidence that dictators mean to compensate the recipient for her vulnerable position in the game. Our results explain why giving decreases under specific conditions designed to increase anonymity and why the same individual may signal very different other-regarding preferences across different rules and/or roles of a game (Blanco et al. 2011).
Keywords: C91; D63; D64; 330; altruism; dictator games; moral preferences; experimenter demand effect; Altruismus; Nichtkooperatives Spiel; Soziale Wohlfahrtsfunktion; Signalling; Test